Space-Terrestrial Integrated Multi-Identifier Network with Endogenous Security - Guohua WEI; Hui LI; Yongjie BAI; Gengxin LI; Kaixuan XING (天地一体化信息网络)
A novel network architecture, named space-terrestrial integrated multi-identifi er network (STI-MIN) was proposed, which was suitable for the environment of space-terrestrial integrated situation.In the following passage, the fundamental theory, Space-Terrestrial integrated routing strategy, identifi er management system and endogenous security mechanism of STI-MIN were depicted.Then prototype experiment progress was summarized and the merit of STI-MIN by comparing with traditional network was analyzed.